EKSPLORASI POTENSI WISATA EDUKASI KEBUN KOPI: PEMBANGUNAN BERKELANJUTAN DI DESA REMPEK DARUSSALAM - Azizah, Rina Ristianty; Jayadi, Ahmad; Fitriani, Fitriani; Dirda, Jaduga Ekanur; Lestari, Imanda; Masyhuri, Zilly Arsyika; Susilayanti, Tuti; Ningrat, Muhammad Dwi; Hartanto, Alief Putra (Universitas Mataram, 2024)
Rempek Darussalam Village, located in Gangga District, North Lombok Regency, is one of the villages with rich agricultural potential, particularly in coffee cultivation. Coffee, as a key commodity, not only has high economic value but also great potential to be developed into an educational tourist attraction. This potential has not yet been fully utilized to support sustainable development in Rempek Darussalam Village. Facing these challenges, the KKN PMD UNRAM 2024 program aims to develop coffee plantation educational tourism as a solution to increase community income and promote local coffee products. This program is implemented through a series of activities, including training in creating educational tourism packages and marketing coffee products. The UNRAM Mataram University KKN group collaborates with local coffee farmers to build tourism facilities, including tour routes and areas for demonstrating the coffee processing. Additionally, training is conducted to enhance the skills of community members involved in communicating with visitors and managing tourism activities. Data collection is carried out through observation, surveys, and KKN activities where coffee plantation educational tourism becomes the main work program. This coffee plantation educational tourism successfully attracted tourists and resulted in increased income for coffee farmers. Evaluation shows that the community has improved skills in managing tourism and marketing coffee products. Furthermore, awareness of the added value of local coffee has increased, positively impacting the village's economy.